EFEKTIVITAS MEDIA AUDIO VISUAL DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI MENGENAL BENTUK PADA SISWA KELAS I SD NEGERI 01 KOTA DEPOK - Yacob Chandra; Rudi Ritonga (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effectiveness of using audiovisual media in improving student learning outcomes in mathematics, specifically in recognizing shapes, in first grade students at SD Negeri 01, Depok City. The problem addressed in this study is students' low understanding of basic geometric shapes such as circles, squares, and triangles, as indicated by average student scores that are still below the minimum completion standard. This study used the Classroom Action Research (CAR) method with the Kemmis & McTaggart model, conducted in two cycles. The research instruments included learning outcome tests, observation, and documentation. The results showed that the use of audiovisual media had a positive impact on improving student learning outcomes, with an average score increasing from 60 to 80 and classical completion from 45% to 85%. This media helps visualize abstract concepts in a more concrete and contextual way, and significantly increases student learning motivation.